Ferromagnetism in layered metastable 1T-CrTe2 - Freitas, Daniele C. (2015)
We have synthesized for the first time the metastable compound 1T-CrTe2. We have done its complete structural characterization and measured its magnetization, specific heat and electrical resistivity between 4 and 330 K. We have also performed detailed band structure calculations. We have found that it crystallizes in the CdI2 structure type and that its electrical resistance follows a metallic behaviour below room temperature. Its magnetization and specific heat curves show that the compound has a transition to a ferromagnetic state at TC = 310 K, with the magnetic moments ordered parallel to the basal plane. From the specific heat measurements and the ferromagnetic solutions obtained from our DFT calculations, we conclude that the ferromagnetism is of itinerant nature.